Data mining and knowledge discovery - Lyons, K. (Ausport, 2005)
At the Australian Institute of Sport (AIS) we also produce a great deal of information. We are currently making a determined effort to store this information in ways that can be used to record, develop and transform performance. In the last year, two initiatives have helped us start this process: